LEGAL PROPAGANDA-AS AN IMPORTANT FACTOR IN RAISING THE LEGAL CONSCIOUSNESS AND CULTURE OF YOUTH - Shadiyev Bekhzod Mirsalimovich (Web of Journals Publishing, 2024)
This article analyzes issues related to raising the legal consciousness and culture of young people and radical reform of the national legal system, formation of legal consciousness and legal culture in society, raising the legal consciousness and legal culture of the population, eliminating problems and shortcomings that prevent the increase in the level of legal literacy of citizens in society.
Keywords: legal culture, exaltation, rule of law, legal consciousness, interest, balance, absorption